Pengaruh Prenatal Yoga Terhadap Penurunan Nyeri Punggung Pada Ibu Hamil Trimester II Dan III Di PMB Bdn. Nurlita Listiana S.ST Sawangan – Depok - Rahmatiar Samtin (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Introduction: In Indonesia, it has been reported that the prevalence of back pain among pregnant women in the third trimester is 70%, with many experiencing back pain during this period. Objective: To determine the effect of prenatal yoga on reducing back pain in pregnant women. Method: Research design: True Experiment, Posttest-Only Control Design. Respondents consisted of 15 pregnant women experiencing back pain, selected using total sampling technique. Results: Before practicing prenatal yoga, back pain levels were as follows: 1–3 (mild pain) in 4 respondents (27%), 4–6 (moderate pain) in 11 respondents (73%), and 7–10 (severe pain) in 0 respondents (0%). After practicing prenatal yoga, back pain levels were: 1–3 (mild pain) in 15 respondents (100%), 4–6 (moderate pain) in 0 respondents (0%), and 7–10 (severe pain) in 0 respondents (0%). Conclusion: Prenatal yoga has a positive effect on reducing back pain in pregnant women in the second and third trimesters.